Sustainable energy systems on near-future Smart Cities: split heat pumps at Bosch Group - Lopes, Mariana Filipa do Souto (2021)
Given the exponential growth of urbanization of cities and greater pressure on essential services, we have been witnessing a paradigm shift towards a more intelligent energy infrastructure, with greater efficiency, new revenue potentials and a cleaner and greener future. In recent years, there has been increasing competitiveness from governments and industry regarding the use of technology in almost all aspects of daily operations. The framework of this is the Smart City study towards a smarter and more sustainable city. This thesis thus aims at understanding the concept of Smart City, with the focus on energy efficiency versus environmental pollution targets. Throughout the thesis, the case of Bosch Termotecnologia S.A. will be studied, regarding to the heat pump industry. The purpose of this work is the ecological analysis of potential refrigerant alternatives for heat pump systems owing to the future limitation of fluorinated refrigerants with a high greenhouse risk.